Penguatan Fungsi Organisasi Melalui Jabatan Fungsional Studi Kasus Sekretariat Daerah Provinsi Kepulauan Riau - Ariza, Raja (Jurnal Ilmu Administrasi Negara (JUAN), 2021)
This study aims to determine how the strategy to strengthen the organization through functional tasks in the regional secretariat of the Riau Islands Province. Most of the administrator positions and all supervisory positions within the Regional Secretariat of the Riau Islands Province will be appointed to functional positions. The number of Supervisory and Position Administrator positions currently available is more than the available functional positions plus the job competency requirements. This research is a quantitative research that uses Leavitt’s Diamond analysis. In Leavitt’s Diamond, an organization is a connected piece, and changing one component can affect another. There are 4 components of the analysis carried out, namely the components of the task (task), people (people), technology (technology), tasks (task). The findings in this study are, 50% of respondents doubt that equalization can strengthen the organization, 68.4% of respondents consider that equalization policy is a new challenge, 64.8% of respondents will be able to fulfill functional position competencies. this is confirmed by 67.6% of respondents who really hope to have a competency development plan and hope to be included in these competency development activities. Based on the above reality, it encourages the Riau Islands provincial government to make efforts to develop human resources through increasing managerial competence, increasing competence, proportionally developing functional position competencies, compiling adaptive and dynamic work maps, compiling Competency Development Needs Analysis (AKPK) documents and conducting selections. internal equalization of functional positions and evaluation of the equalization of positions. In the future, it is hoped that there will be further research on evaluating the competency gap of positions after the implementation of the equalization of positions.